Nightlines - Jordan, Neil, 1951- (New York : Random House, 1995)
Released from prison in Madrid during the Spanish Civil War in exchange for political intelligence, Donal Gore returns to a fractured Ireland and a triangular relationship with his father and his young beautiful stepmother.
Originally published: London : Chatto & Windus, 1994 as Sunrise with sea monster
Includes glossary.
Adult
Adult
Library Journal
Booklist starred
Keywords: Fathers and sons -- Fiction; Stepmothers -- Fiction; Stepmothers -- Fiction; Historical fiction; Father-son relationship -- Fiction; Ireland -- History -- 1922- -- Fiction; Ireland -- History -- Fiction; Historical fiction; Political fiction